METHANOL DEHYDRATION INTO DIMETHYL ETHER (DME) SIMULATION IN FIXED BED REACTOR - Yadi Santoso, Mochtar
Based on National Energy Scheme (RUEN) 2017, number of liquefied petroleum gas (LPG) import will increase due to deficit of LPG supply in Indonesia. DME could be used in LPG mixture as an alternative to fulfill national LPG demand. DME has few advantages such as LPG-like physical properties, also not as harm to environment because its combustion produces less to zero NOx and SOx. DME could be produced through methanol dehydration process, which is favorable because it is easier to optimize. Research about methanol dehydration on fixed-bed reactor need to be done to obtain the effect of operating condition such as temperature and concentration on conversion and bed temperature profile along the reaction. This research uses the help of Matlab and Aspen HYSYS software to calculate equilibrium conversion using thermodynamics approach and graph methanol conversion and bed temperature profile in fixed-bed reactor. Equilibrium calculation is done for methanol dehydration reaction, also side reactions such as methanol decomposition into syngas, water gas shift reaction, and DME dehydration into ethylene. Methanol dehydration reaction in fixed-bed reactor simulated in isothermal and adiabatic reactor. All analysis is done through variations on the feed temperature (300-350°C) and concentration (0,01-0,04 mol/m 3). Based on thermodynamics approach, side reactions are more dominant than methanol dehydration. Usage of ?-alumina catalyst intended to avoid the side reactions, because this catalyst is selective to DME production. Methanol dehydration on ?-alumina yielded 42,20% methanol conversion at 350°C while only 9,86% converted at 300°C. Increase on feed concentration from 2 mol/m 3 to 10 mol/m 3 can increase methanol conversion from 31,80% to 42,20% at 350°C. Based on methanol dehydration simulation on fixedbed reactor, the reaction will be faster and bed temperature will increase significantly in higher feed temperature and concentration.